2019
DOI: 10.1360/ssc-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in film-based fluorescence sensing

Abstract: A new spirofluorene-based nonplanar PBI-dyad and its utilization in the film-based photo-production of singlet oxygen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(91 reference statements)
1
3
0
Order By: Relevance
“…Since then, coastal reclamation and land use have advanced to the stage of being a priority for ecological conservation. Such findings were in line with earlier studies that identified periodic coastal reclamation as the main force behind neighborhood urbanization and economic growth (Liu & Li, 2020;Meng et al, 2017).…”
Section: Process Of Coastal Reclamationsupporting
confidence: 93%
“…Since then, coastal reclamation and land use have advanced to the stage of being a priority for ecological conservation. Such findings were in line with earlier studies that identified periodic coastal reclamation as the main force behind neighborhood urbanization and economic growth (Liu & Li, 2020;Meng et al, 2017).…”
Section: Process Of Coastal Reclamationsupporting
confidence: 93%
“…The composite material obtained by doping the xerogel into the polymer matrix has the advantages of easy processing and good flexibility and can enhance the practical application of the gel [ 32 , 33 ]. PMMA has good UV resistance, chemical durability, and good mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent film sensors are widely considered, due to their advantages, such as convenient portability, real-time detection, and no pollution to the system, for testing [ 32 , 33 , 34 , 35 , 36 , 37 ]. Compared with the solution and powder detection forms, the adjustable shape, size, and flexibility of the fluorescent film makes it have wider application prospects.…”
Section: Introductionmentioning
confidence: 99%
“…These vapor chemosensors are usually fabricated from fluorophores or chromophores as active sensing materials (also known as probes) in the form of solid films, relying on the rational design of the molecular structures. Compared to those molecule or particle-based sensors in solution-phase detection, these sensing films are usually prepared by immobilization of fluorescent or colorimetric sensors (in molecule, particle or fibril form) on suitable solid substrates, providing advantages in terms of their reusability and reproducibility, which are two crucial factors for practical applications and actual device development of chemosensors [14][15][16].…”
Section: Introductionmentioning
confidence: 99%